2017
DOI: 10.1042/ebc20170056
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting cancer vulnerabilities: mTOR, autophagy, and homeostatic imbalance

Abstract: Mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) at lysosomes plays a pivotal role in cell growth control where an array of large multiprotein complexes relay nutrient, energy, and growth signal inputs through mTORC1. In cancer cells, such regulation often becomes disconnected, leading to uncontrolled cell growth and an elevation in cellular stress. Consequently, cancer cells often lose homeostatic balance as they grow in unfavorable conditions, i.e. when nutrients and energy are limited yet mTORC1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…To valid this hypothesis, we treated hFOB 1.19 cells with increasing doses of CNR2 ligands HU308 and JWH133, and found that the autophagic flux was gradually enhanced. mTOR, a serine/threonine protein kinase, is a core component of mTOR complex 1 (mTORC1), the activation of which potently inhibits autophagy [26,27]. Administration of mTOR inhibitor (rapamycin) or genetic ablation of mTOR has been reported to preserve the function of osteoblasts and osteocytes, and prevent bone loss [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…To valid this hypothesis, we treated hFOB 1.19 cells with increasing doses of CNR2 ligands HU308 and JWH133, and found that the autophagic flux was gradually enhanced. mTOR, a serine/threonine protein kinase, is a core component of mTOR complex 1 (mTORC1), the activation of which potently inhibits autophagy [26,27]. Administration of mTOR inhibitor (rapamycin) or genetic ablation of mTOR has been reported to preserve the function of osteoblasts and osteocytes, and prevent bone loss [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Even though many water soluble rapalogs were tested in cell and animal models, their effect in the clinic is generally only modest or weak (Kim and Guan, 2019). In some patients, rapalog usage inadvertently promotes cell survival by enhancing the PKB/Akt activity or by activating autophagy which promotes survival in oxygen-deprived microenvironments (Tabernero et al, 2008;Palm et al, 2015;Johnson and Tee, 2017). In some cases, these effects can be countered by combining rapalogs with an autophagy inhibitor hydroxychloroquine (Rangwala et al, 2014).…”
Section: Rapalogsmentioning
confidence: 99%
“…Hypoxia and growth factors can induce the expression of hypoxia inducible factor 1α (HIF-1α) [54] , the downstream blood vessels endothelial growth factor (VEGF) transcription [55] . The PI3K/AKt pathway activation can up-regulate the expression of HIF-1α and VEGF, thus making endothelial cell migrate to form new blood vessels; (2) promoting tumor invasion and metastasis: Johnson and Tee [56] have shown that PI3K/ AKt/mTOR activation can make the downstream molecules p70s6k phosphorylated to make actin filament remodel and to enhance the ability of tumor cells to move, thus increasing the invasion and metastasis of cancer cells. Activation of Akt increases the transcriptional activity of NF-κB and the motor function of tumor cells, which facilitates invasion of cancer cells [57] .…”
Section: Signaling Pathwaysmentioning
confidence: 99%